CPM472 : New media studies / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course explores fundamental concepts of new media as new tools to be implemented and use by the future generation. The subject is emphasize in exploring the evolution of digital media technologies. This is an interdisciplinary course that includes Photography as communication, Information Technologies and design. Students will use digital media technology throughout the course, providing them with practical experience with new media. Student will apply the art of new media design, by designing, planning and creating new media content.